1976
DOI: 10.1111/j.1467-9450.1976.tb00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of visual acuity in preschool children

Abstract: Abstract.— Problems in testing visual acuity of preschool children were discussed with regard to choice of optotype and test distance, illumination, instruction and response indicator, and the motivational aspect of the test situation. A test situation conforming to these requirements for measuring visual acuity was arranged for testing of preschool children, using a discrimination learning paradigm with simultaneous presentation of the cues. The test figures were two Landolt Cs of equal size but one with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…Kothe and Regan also concluded that both uncrowded and crowded acuity improved in parallel between the ages of 4 and 11 years. This finding of the continued development of uncrowded acuity beyond the age of around 6 years conflicted with the conclusions of some previous authors, [21][22][23] who reported high levels of single optotype (uncrowded) acuity at young ages with little development thereafter (see also ref. 24 ).…”
contrasting
confidence: 75%
“…Kothe and Regan also concluded that both uncrowded and crowded acuity improved in parallel between the ages of 4 and 11 years. This finding of the continued development of uncrowded acuity beyond the age of around 6 years conflicted with the conclusions of some previous authors, [21][22][23] who reported high levels of single optotype (uncrowded) acuity at young ages with little development thereafter (see also ref. 24 ).…”
contrasting
confidence: 75%
“…Furthermore, the 3 m test distance reduces test times and increases patient co-operation particularly in poorly motivated children (Sheridan, 1960;Smorvik and Bosnes, 1976;Pickert and Wachs, 1980). A regular geometric progression of letter sizes is employed whose ratio is equal to 10 Z10 (0.1 log unit).…”
Section: Methodsmentioning
confidence: 99%
“…Glasgow Acuity Cards are viewed directly at a distance of 3 m, since it has been suggested that some children may perform slightly better at this reduced distance for psychological reasons (Kitao, 1960;Sheridan, 1974;Brant and Nowotny, 1976). Furthermore, the 3 m test distance reduces test times and increases patient co-operation particularly in poorly motivated children (Sheridan, 1960;Smorvik and Bosnes, 1976;Pickert and Wachs, 1980). A regular geometric progression of letter sizes is employed whose ratio is equal to 10 Z10 (0.1 log unit).…”
Section: Methodsmentioning
confidence: 99%